Agroclimatic and Management Interactions Shaping Genetic and Agronomic Performance of Potato (Solanum tuberosum L.) under Sudan Savanna Field Conditions (Sahel Journal of Life Sciences FUDMA, 2025)
Potato (Solanum tuberosum L.) cultivation is extending into the Sudan Savanna of Nigeria; however, productivity is limited by inadequate knowledge of optimal planting time, seed type, and plant density. A two-year field study (2017/18 and 2018/19) was conducted at Bayero University, Kano, and Aliko Dangote University of Science and Technology, Wudil, to evaluate the effects of planting date, propagation method, and plant density on growth and yield attributes of potato. The experiment employed a fractional factorial design with five planting periods (late October to early December), two seed types (whole and cut tubers), and three plant densities (33,333, 43,333, and 66,666 plants haâ»Â¹). Results indicated that planting date and location significantly influenced all measured traits (p < 0.001). Late October planting resulted in the earliest emergence (14.6 days), fastest maturity (83.8 days), tallest plants (42.2 cm), and highest leaf and branch numbers, while each delay in planting progressively reduced vegetative growth and yield. High plant density (66,666 plants haâ»Â¹) produced more branches and greater tuber yield (16.2 t haâ»Â¹) than medium or low densities. The propagation method had no significant effect on any trait measured. Environmental variation also played a key role, as cooler temperatures and higher soil phosphorus at Wudil enhanced plant growth and tuber productivity compared with Kano. Overall, the best performance across morphological and yield parameters was achieved with late October planting at high plant density using cut seed tubers. These findings provide a framework for improving productivity and sustainability of potato production in Sudan Savanna.